THE TIMELINESS OF FINANCIAL REPORTS SUBMISSION: PROFITABILITY AND SOLVABILITY IN IDX’S MANUFACTURING COMPANIES (CAHIERS MAGELLANES-NS, 2024)
Timeliness in financial reporting is an important element that not only reflects the company's accountability, but also influences investors' and creditors' perceptions of the company's performance. Research studied aims to test the effect of profitability and solvency on the timeliness of financial report submission. The population used for the study is all manufacturing entities operating in the consumer goods industry sector which have been registered on the Indonesia Stock Exchange that publish audited annual financial reports and announced on the Indonesia Stock Exchange for the period 2019-2023 as many as 41 companies. The sample selected was 21 companies using the purposive sampling method. Technique data collection using documentation, is a way to download annual financial information of manufacturing entities in the consumer goods industry in 2019-2013 on the Indonesia Stock Exchange from an official website called web.idx.id, \Analyze data using the SPSS. The results of the study indicate that profitability as measured by Return on Assets (ROA) does not have a significant effect on the timeliness of financial reporting, with a significance value of 0.390. This means that the sig value of 0.390 is greater than 0.05, so the hypothesis stating that there is an effect of profitability on the timeliness of reporting cannot be accepted. Likewise, solvency as measured by Debt to Asset Ratio (DAR) also does not show a significant effect on the timeliness of financial reporting, with a significance value of 0.371. This shows that solvency does not contribute to the timeliness of financial reporting, because the sig value of 0.371 is also greater than 0.05.